Aggressive fibromatosis (desmoid tumor) associated with breast implant: literature review and presentation of three new cases - Aloísio Ferreira da Silva Filho; José Carlos Ribeiro Resende Alves; Erick Horta Portugal; Rebeca Paohwa Liu da Fonseca; Augusto César de Melo Almeida; Nárlei Amarante Pereira; Frederico Lins e Silva; Eduardo Ferreira Calsavara; José de Souza Andrade Filho (Revista Brasileira de Cirurgia Plástica, 2017)
INTRODUCTION: Fibromatoses consists of the proliferation of fibrous tissue, in the form of bands or nodules, associated with fasciae and aponeuroses. The aggressive variety, previously denominated desmoid tumor, behaves similarly to malignant neoplasm, with local destruction of tissues, without, however, producing metastases. METHODS: A literature review was carried out from 1979 to January 2017. Data from three patients, operated between May 2010 and August 2015, were reviewed. Age, implant characteristics, route of introduction, time elapsed between implantation and fibromatosis, surgical treatment, clinical follow-up and results were observed. RESULTS: Twenty-four papers were found in the literature reporting aggressive fibromatosis of the chest wall associated with silicone breast implant. In these studies, 34 cases were reported. Three new cases of aggressive fibromatosis associated with silicone breast implant are now presented. These cases were successfully treated by extensive resection of the chest wall, including skin, musculature, ribs, endothoracic fascia, and parietal pleura. The reconstruction was successful, performed with alloplastic mesh (Prolene®) covered by muscular flap in two cases and local skin flap in one case. CONCLUSION: The association of aggressive fibromatosis and breast implant is rare. The treatment should consist of extensive surgery, removing the breast implant and the entire area of the capsule around it, part of breast, together with the underlying ribs, intercostal muscles, endothoracic fascia and parietal pleura. The reconstruction should be made with an alloplastic mesh, covered by muscular flaps or local skin flap.